2013
DOI: 10.1890/13-0915.1
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected redwood mortality from synergies between wildfire and an emerging infectious disease

Abstract: Abstract. An under-examined component of global change is the alteration of disturbance regimes due to warming climates, continued species invasions, and accelerated land-use change. These drivers of global change are themselves novel ecosystem disturbances that may interact with historically occurring disturbances in complex ways. Here we use the natural experiment presented by wildfires in redwood forests impacted by an emerging infectious disease to demonstrate unexpected synergies of novel disturbance inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 38 publications
(55 reference statements)
2
90
0
Order By: Relevance
“…In our plots, fire intensity was positively related to the amount of fine canopy fuels associated with recently killed trees and decreased as these materials move from the canopy to the soil surface [18]. In contrast, fire-caused mortality of redwood, a species that is resilient to P. ramorum and typically also resilient to fire, increased with greater accumulation of ground fuels [59]. This pattern suggested that disease-generated fuels accumulated to the point that damage to tree root systems or cambium tissue was substantially increased.…”
Section: Disease-disturbance Interactionsmentioning
confidence: 66%
See 3 more Smart Citations
“…In our plots, fire intensity was positively related to the amount of fine canopy fuels associated with recently killed trees and decreased as these materials move from the canopy to the soil surface [18]. In contrast, fire-caused mortality of redwood, a species that is resilient to P. ramorum and typically also resilient to fire, increased with greater accumulation of ground fuels [59]. This pattern suggested that disease-generated fuels accumulated to the point that damage to tree root systems or cambium tissue was substantially increased.…”
Section: Disease-disturbance Interactionsmentioning
confidence: 66%
“…Landscape-scale disturbances such as wind, fire, or land use can (i) modify the impacts of a disease [22,61]; or (ii) can be influenced by disease in a manner which increases or decreases the ecological impacts of these disturbances [59]. In both cases, the potential to magnify the ecological impacts of either disturbance can have important management implications [16,17], but the mechanistic processes driving these impacts are quite different.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…al., 2003), prevalence and magnitude of wildfire (Westerling et al, 2011), and occurrence of insect pests and pathogens (Crowl, Crist, Parmenter, Belovsky, & Lugo, 2008;Metz, Varner, Frangioso, Meentemeyer, & Rizzo, 2013). A recent study of the endemic flora of the California Floristic Province by Loarie et al (2008) suggests that under extreme and moderate scenarios of climate change that the suitable habitat for many species native to California will shift from inland to coastal areas, and that coastal species are predicted to undergo northward range shifts.…”
mentioning
confidence: 99%